Disputes and issues relating to sale and purchase land in Malaysia - Syed Abdul Kader, Sharifah Zubaidah (s.n, 2012)
This research discusses the sale of land or building or parcel in a sub-divided building or land parcel in Malaysia. This research will highlight selected issues and disputes arising out of land as the subject matter of sale. Issues relate to matters that need to be considered and dealt with by the solicitor in ensuring the success of the transaction whilst disputes relate to differences between the vendor and the purchaser that may lead to the seeking of remedies arising from the breach of obligations under the contract